Fra underjordiske dysser til synlige trapezformede anlæg – om stenaldergravene ved Harreby i Sønderjylland - Jørgensen, Erik (Kuml, 2006)
From Subterranean Dolmens to Visible Trapezium-shaped Structures On the Stone Age Graves from Harreby in North Schleswig/South Jutland In 1934 and 1936, four Stone Age graves were found at Harreby west of Gram in North Schleswig: three dolmen chambers and one flat burial. They were considered part of a flat burial graveyard. New investigations at Harreby have unmistakably shown that the dolmen chambers found by C.M. Lund and Therkel Mathiassen do not belong to any flat burial site. Thus, they cannot be characterized – as Therkel Mathiassen did – as subterranean, hidden underneath the Stone Age surface. The excavations have clearly established that the graves were originally surrounded by four oblong trapezium-shaped structures (I-IV) on the sloping side of the Fladså river valley. Structure I and IV contained only one grave, whereas structure II and III contained three graves each. All structures had a grave positioned in the wide west end. Structure I. This structure consisted of a 53-m long and 3-6-m wide trapezium-shaped mound constructed by sand and gravel (Figs. 14 and 23). The fairly low mound had been surrounded by large kerbstones, some of which were still in position. The wide west end had contained a dolmen chamber (grave A) built of four side stones placed in an hollow dug approximately 1.3 m into the ground. On level with the old field surface, the hollow had an almost square outline and measured 3.4 x 4.2 m. At floor level, the chamber would have been approximately 1.9-m long and 1.1-m wide. A fire had been lit at the bottom of the hollow before a c.7-cm thick layer of white, burnt flint had been spread across it as a floor layer. A single amber bead was found on top of the flint layer (Fig. 15.7). An unpolished thin-butted flint axe; two thick-butted flint axes with narrow blades; two flint blades, and an amber bead were found near the bottom in the rummaged chamber fill (Fig. 15.1-6). The thin-butted flint axe, which belongs to type IV, must be connected with the primary funeral, which took place either towards the end of the Early Neolithic or the beginning of the Middle Neolithic Period (Nielsen 1977). However, the narrow-bladed, thick-butted flint axes originate from secondary burials made during the late Funnel Beaker Culture in the Middle Neolithic Period. Neither the two flint blades nor the fragmented amber bead can be dated precisely. Structure II. Structure II was situated immediately next to structure I and consisted of a long, low, trapezium-shaped mound (Fig. 22), probably also originally surrounded by kerbstones. The structure was widest towards the west, where it had a width of 9 m. It is difficult to state precisely how long the trapezium-shaped mound was initially, as the major part of it was situated outside the area excavated by C.M. Lund and Th. Mathiassen in the 1930s. In all probability, the east end of the mound was placed between grave 3 and structure I. Although no fills or end ditch were observed during the excavation in 1983, this area contained colour differences in the fill that seemed to indicate the end of the mound. This indicates that the trapezium-shaped structure II was 41 metres long. The wide west end of the structure had contained a four-sided dolmen chamber (grave B) built from two bearing stones in each long side and one in each narrow side. The chamber – the longitudinal direction of which ran transversely to that of the mound – was sunk 20 cm into the subsoil and surrounded by a stabilising packing of clay and stones. The floor layer in the chamber consisted of white, burnt flint, some places still in situ, on top of which an amber bead was found (Fig. 18.B2). The chamber had also contained a thin-butted, four-sided, polished, thin-bladed flint axe (Fig. 18.B1) found in the disturbed chamber fill. A large, plump, four-sided, polished, thick-butted flint axe from the Single Grave Culture (Fig. 18.B3) was found in disturbed fill just above the clay and stone packing towards the north. From the fill around the axe, which differed from the disturbed chamber fill, it is difficult to determine whether the flint axe was dug up from dolmen chamber B or from another grave. The dolmen chamber (chamber 1), which gave cause for the excavation in 1934, was situated inside this structure, 25 metres from the west gable of the mound. The grave chamber was built from four inward-leaning stones placed in such a way that the top of the end stones rested against the side stones. The inner dimension of the chamber at floor level was 1 x 2.6 m. The chamber fill contained a single unornamented pottery sherd and the tip of a flint dagger (Fig. 29.d). Grave 3, which was situated in the east end of the structure and transversely to its longitudinal direction, was a stone cist built from ashlar-like stones and surrounded by a stone heap. However, the stones from the grave were preserved only in the north end of the grave. Stacks of smaller flat stones, some of which had fallen into the grave, showed that the gaps between the ashlars had been filled with dry stonewalling. The bottom of the grave, which measured up to 1 m across and had a length of 2.8 m, had been covered with white, burnt flint. Two earthenware vessels and an amber bead were found in the north end (Fig. 6.a-c). An ornamented sherd and a fragmented amber bead were found later in the removed fill (Fig. 6.d-e). Structure III. Another trapezium-shaped, long mound was situated immediately north of structure II, partly overlapping its northern end (Figs. 22 - 23). It had been 35 m long and 5 and 7.5 m wide in its east and west end respectively. Stone traces and ditches registered during the investigations in 1983 and 1990, as well as the long line of stones (Fig. 8) and other stone rows – such as the north and south sides of grave 4 and 6, which appeared during the excavations by C.M Lund and Th. Mathiassens in the 1930s – show that the mound was encircled by kerb stones. A four-sided dolmen chamber with the same longitudinal direction as the mound was probably situated in the wide west end of the long mound (grave C). A fire had been lit on the bottom of the c.1.4-m wide and 2.3-m long chamber before it was covered with white, burnt flint. In the west end of the grave, an amber bead was found in situ in the upper part of the burnt flint, and a flint blade was found in the disturbed chamber fill (Fig. 18.C1-2). The other dolmen chamber excavated by C.M. Lund (chamber 2) was situated centrally in the eastern half of the mound, inside structure III. The chamber, the longitudinal direction of which was parallel to that of the mound, was built from four stones. The two in the long sides of the grave were vertical, whereas the end stones leaned inwards, with the tops resting against the side stones. No artefacts were found in the chamber fill or on the grave bottom, which measured 0.7 x 1.65 m. About midway between dolmen chamber C and 2 was yet another dolmen chamber (chamber 5). This chamber was placed in a hollow dug 2 metres into the ground and built from four bearing stones and a cover stone, the top of which was 30 cm underneath the soil surface. Also in this chamber, the bearing stones were leaning inwards, with the top of the end stones resting against the side stones. The chamber bottom, which measured 1.0 x 2.5 m, was situated transversely to the longitudinal direction of the mound. No grave goods appeared in the chamber. Structure IV. The trapezium-shaped ditch structure was for the main part hidden underneath structure III. Only the wide western end, measuring up to 3.4 m and comprising grave D, was situated outside it. The original length of the structure is difficult to estimate, as its east end is situated outside the area excavated in the 1930s. However, provided the structure had a real trapezium-shaped outline and an east end no less than one metre wide, then the structure would have had a length of approximately 22 m, as indicated on Fig. 22. This means that the structure was not just covered by structure III and its mound, but also that it was disturbed by the pit dug for chamber 5. Grave D, situated in the wide end of the structure, was partly disturbed by the western cross-ditch of structure III, and partly by modern cuts (Fig. 19). The grave was not a stone cist grave, as the grave bed consisting of white, burnt flint was enclosed by a frame made from at least two layers of boulders, which had the flat sides turned inwards. The stone frame had been surrounded by a stone heap, which was again framed by the surrounding ditch. Three amber beads, a flint blade, and an earthenware pot were found in situ on top of the white, burnt flint covering the bottom (Fig. 20). Structure IV was probably covered by a low mound, and the ditch encircling it probably held woodwork, as indicated by the stones in the western cross ditch. The dating of the structures. Structure IV was probably the first one to be built, as indicated by the beaker (Fig. 20.5) found in the grave (grave D), which is ornamented in the best Fuchsberg style (Andersen and Madsen 1977). This dates the construction of the structure and the burial to the very last part of the Early Neolithic, or more precisely, the Fuchsberg phase around 3.400 BC (2.630-2.810 C-14 BC.) (Andersen 1999). On the other hand, it is possible that Structure I is the oldest. The thin-butted flint axe (Fig. 15.1), found on the dolmen site (grave A) in the west end of the structure and possibly originating from the primary burial, belongs to type IV. This type originates predominantly from the Early Neolithic period C (Nielsen 1977), which includes the Fuchsberg phase, although it also occurs in the Middle Neolithic period I. This axe type may even be older than the Fuchsberg phase (Klassen 2004). The relative construction time for structure II, III, and IV give no chronological problems. Of these, structure IV is the oldest. From the sections made through the coinciding north and south ditches from structure III and II respectively, it clearly appeared that structure III had been dug into structure II. The chronological order of the construction of the three structures is thus: structure IV was built first, then structure II, whereas structure III was built last. However, without these stratigraphic observations it would have been difficult to estimate the construction time for structure II and III, as the grave goods found in grave B and C respectively – the supposed primary graves – do not allow a precise dating. The thin-bladed thin-butted flint axe (Fig. 18.B1) found in grave B within structure II belongs to a type found in several early Neolithic graves, but which is also known from finds belonging to the early Middle Neolithic period (Nielsen 1977). The same applies to the two tubular amber beads (Figs. 18.B2 and 18.C2) found in the two graves. Erik Jørgensen Haderslev Museum Translated by Annette Lerche Trolle